2021
DOI: 10.3390/ijerph19010199
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Depressive Symptoms in Adults with Multiple Sclerosis: A Scoping Review

Abstract: Background. Vitamin D deficiency has been correlated with Multiple Sclerosis (MS) risk and disease activity. There is some controversy as to whether vitamin D could have an impact on depressive symptoms in people with MS (pwMS). The aim of this scoping review was to evaluate the association between vitamin D status and depressive symptoms in pwMS. Methods. We searched databases to include studies published up to March 2021 to provide an overview of the available evidence on the correlation between vitamin D st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Some limitations were also shown, i.e., a small number of included studies and publication bias. Researchers have shown that vitamin D supplementation supports the treatment of MS patients and reduces the appearance of depression symptoms [58][59][60][61], although studies on this issue are contradictory and inconclusive [62]. Future research on vitamin D and MS depression symptoms should include patients with actual depression symptoms at baseline and include confounders such as exposure to the sun.…”
Section: Vitamins Vitamin Dmentioning
confidence: 99%
“…Some limitations were also shown, i.e., a small number of included studies and publication bias. Researchers have shown that vitamin D supplementation supports the treatment of MS patients and reduces the appearance of depression symptoms [58][59][60][61], although studies on this issue are contradictory and inconclusive [62]. Future research on vitamin D and MS depression symptoms should include patients with actual depression symptoms at baseline and include confounders such as exposure to the sun.…”
Section: Vitamins Vitamin Dmentioning
confidence: 99%
“…Various factors such as sleep disturbances, endocrine dysfunction, and mood disorders can contribute to the development or exacerbation of fatigue, necessitating careful investigation for the potential underlying causes [ 45 ]. The association with anxiety and depression could be explained by the underlying pathogenic mechanisms such as alteration of HPA [ 46 ] and noradrenergic pathways as well as the involvement of pro-inflammatory cytokines [ 30 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal inflammation in people with MS (PwMS) and depression leads to increased neurodegeneration and thus progression of disability [2]. However, depression can also indicate inflammatory reactivation in MS [3].…”
Section: Introductionmentioning
confidence: 99%